Profil Penggunaan Obat Pasien Hipertensi Esensial Di Instalasi Rawat Jalan Rumah Sakit Umum Daerah I Lagaligo Kabupaten Luwu Timur Periode Januari-Desember Tahun 2014: Profile of Drug Use In Patients With Essential Hypertension at Outpatient Installation General Hospital I Lagaligo Luwu Timur Regency Period of January-December 2014 - Senfri Tandililing; Alwiyah Mukaddas; Ingrid Faustine (Universitas Tadulako, 2017)
This study aimed to determine the demographic and clinical characteristics and profile of drug use in patients with essential hypertension at outpatient installations I Lagaligo General Hospital East Luwu Regency period January-December 2014. The research method is descriptive done retrospectively by collecting secondary data from medical records essential hypertension patients undergoing outpatient treatment at General Hospital I Lagaligo East Luwu Regency period January-December 2014. The number of samples in the study were 145 patients. The dominant demographic characteristics of women that 87 patients (60%), age range 41-60 years (55.86%), hypertension grade 1 (73.78%), a class of drugs most widely used is a calcium antagonist (45.45%), the type of drug amlodipine (44.27%), 100% tablet dosage forms, rules of use 1 to 2 times a day, namely amlodipine monotherapy (63.08%), the combination of two antihypertensive amlodipine-hydrochlorothiazide (38.61%), the combination of three antihypertensive amlodipine-hydrochlorothiazide-Captopril (69.57%). The results obtained in accordance with an algorithm treatment of hypertension according to Joint National Committee (JNC 7).